Foreign Direct Investment and Productivity in Peru - Chong Ríos, Alexci Igor (2019)
The objective of this study is to find empirical evidence if the FDI measured through companies that have 15% more than foreign capital has contributed to improve the productivity of the industry in general. As well, as verify if these companies have greater profitability than companies with national capitals do. On the other hand, we seek to find evidence if there are spillovers of productivity towards national companies. The study finds companies with foreign capital with higher productivity and presence of spillovers from companies with foreign capital greater than 50%. Less than this percentage, there is no statistical significance.